Uji Daya Hambat Ramuan Herbal (Bawang Putih, Daun Sirih, dan Kayu Manis) Terhadap Pertumbuhan Bacillus subtilis dan Escherichia coli - Muhammad Nur Hidayat; Amriana Hifizah; Ismawati Asmar (State Islamic University (UIN) Alauddin, 2013)
This study aims to determine the inhibitory activity of garlic, betel leaf and cinnamon herbal remedy made to the growth of B. subtilis and E. coli, and to know the long fermentation of the best herbs to inhibit the growth of B. subtilis and E. coli. This research was conducted in the Laboratory of Microbiology and Animal Health High School Agricultural Extension (HSAE/) Gowa. The treatment is given as follows: The herb is fermented for 0 days without EM4 (control) P0; herb fermented for 0 days without EM4 P1; herb that is fermented for 7 days with EM4 P2; herb that is fermented for 14 days with EM4 P3; herb fermented for 21 days at EM4 P4. The data obtained were processed using Completely Randomized Design (CRD) and what if the test significant, then continued with the smallest Significant Difference Test (SDT). Results of analysis of variance showed that the treatment significantly (P<0.05) against on the growth of B. subtilis and E. coli. The conclusion of this study is, materials that are made of herbal ingredients (garlic, betel leaf and cinnamon) has a diameter of inhibition zones on treatment significantly (P<0.05) on the growth of B. subtilis and E. coli. and long fermentation excellent for growth resistor B. subtilis and E. coli is at P3 treatment 14 days fermentation. Keywords: Herbal Remedy (Garlic, Betel Leaf and Cinnamon), B. subtilis, E. coli.